Evaluation of the “Nursing Process Teaching Information System - SIEPENF” software (Research, Society and Development, 2020)
Evaluate the software "Information System for Teaching the Nursing Process – SIEPENF", from the perspective of students in the nursing course Nursing at the Federal University of Pernambuco - Vitória de Santo Antão Campus. This is a descriptive, exploratory study with a qualitative and quantitative approach, carried out through a questionnaire created from the ISO / IEC 25010: 2011 standard, which deals with software engineering - product quality. Participated in the study 14 students of the nursing course, who have already taken the discipline Nursing Care Systematization. The “Nursing Process Teaching Information System software – SIEPENF” received favorable evaluations for the characteristics proposed by the standard. Information technologies contribute greatly to the work process of nursing professionals, which is why it is necessary to invest more in studies that aim to computerize the nursing process.